Comparison of reproductive performance, mortality rate and productivity of Menz and Horro sheep breeds of Ethiopia - Asmamaw, B.R. (Wageningen University & Research, 2001)
Ewe reproduction, productivity and lamb mortality were studied in grazing Horro and Menz ewes treated with FGA intravaginal sponges in the wet or dry season to compare the performance of the two indigenous Ethiopian highland breeds. There was a significant (p<0.001) difference in fertility rate (79 vs. 70%), weaning rate (0.92 vs. 0.78) and mortality rate (13% vs. 27%) between Menz and Horro ewes, respectively. The difference in lambing rate between Menz and Horro ewes was also significant (p<0.01) (0.81 vs. 0.76, respectively). There was no significant difference (p>0.05) of litter size between the two breeds. The productivity (total age and sex adjusted live weight weaned or Index I) of Horro sheep was higher (P<0.001) than that of Menz (9.06kg vs.8.00kg). When expressed in relation to dam postpartum weight, Horro and Menz sheep had similar (P>0.05) productivity (292.3 vs. 291.3 gm/kg). Using an animal model, the heritabilities for mortality, lambing, weaning rate and litter size were 0.03, 0.11, 0.03, and 0.116, respectively.